Eficacia de los fertilizantes orgánicos y su aplicación en el cultivo de tomate (Solanum lycopersicum) en Ecuador - Yépez Bricio, Johann Estiven (2025)
In Ecuador, agriculture is a fundamental part of economic growth, within the crops grown in the country is the cultivation of tomato (Solanum lycopersicum), this agricultural crop has become one of the most important sources of income for farmers in rural areas, to all this is added that it is one of the vegetables with high marketing index both domestically and abroad so organic fertilizers have become the most used for the development of this crop. Based on this approach, the research was carried out with the objective of determining the effectiveness of fertilizers in the tomato crop in Ecuador, its impact and soil quality. For which the descriptive research method was used, through the use of scientific research such as articles, theses, reports, among others. The results presented in the study describe organic fertilizers of vegetable, animal and mineral origin as the main fertilizers used in tomato crops, because they generate a minimum environmental impact and favor the structure and fertility of the soil and provide nutrients (nitrogen, phosphorus, potassium, among others) which are efficient and contribute to the proper development of the plant. The correct management of techniques and application rates of organic fertilizers in the plantation result in good yield and quality of the tomato crop (S. lycopersicum) in Ecuador.